3(x-9)=4x-9

Simple and best practice solution for 3(x-9)=4x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-9)=4x-9 equation:


Simplifying
3(x + -9) = 4x + -9

Reorder the terms:
3(-9 + x) = 4x + -9
(-9 * 3 + x * 3) = 4x + -9
(-27 + 3x) = 4x + -9

Reorder the terms:
-27 + 3x = -9 + 4x

Solving
-27 + 3x = -9 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-27 + 3x + -4x = -9 + 4x + -4x

Combine like terms: 3x + -4x = -1x
-27 + -1x = -9 + 4x + -4x

Combine like terms: 4x + -4x = 0
-27 + -1x = -9 + 0
-27 + -1x = -9

Add '27' to each side of the equation.
-27 + 27 + -1x = -9 + 27

Combine like terms: -27 + 27 = 0
0 + -1x = -9 + 27
-1x = -9 + 27

Combine like terms: -9 + 27 = 18
-1x = 18

Divide each side by '-1'.
x = -18

Simplifying
x = -18

See similar equations:

| 5x+18-7=x-1 | | x/30=11/15 | | (6/7xy^7)(1/5x^2y^2) | | x+y=193.2 | | 0.75x*2.35y= | | y+8x=0 | | x/12-5=13/24 | | x^2+-8x+16=0 | | ((Y^3)/(-2z))^2 | | 2x+5y-z=8 | | 36=-6/7w | | 20/n-2=138 | | 6+35x=28x+15 | | 141=4x-48+8x-27 | | 3n+6=120 | | 2x+3y+z=16 | | Cos-1=9/18 | | 1.3x=260 | | 1(22y+5)= | | 4x+3y+z=24 | | 0.1(x+40)+1.1x=40 | | 12x^2+18x-82=0 | | y/11-3=2 | | 8/x-7=-12 | | 6(2x+11)=6x+30 | | 2(a+4b)=12 | | 1/x-4=-3 | | 2x-42=7x-22 | | 3444/654 | | 3434/34 | | 32/5solution | | 4x+1+x-47+x-38=360 |

Equations solver categories